Atherosclerotic coronary lesions with inadequate compensatory enlargement have smaller plaque and vessel volumes: observations with three dimensional intravascular ultrasound in vivo. Issue 2 (1st February 1998) - von Birgelen, C; Mintz, G S; de Vrey, E A; Kimura, T; Popma, J J; Airiian, S G; Leon, M B; Nobuyoshi, M; Serruys, P W; de Feyter, P J
Abstract : Objective: To compare vessel, lumen, and plaque volumes in atherosclerotic coronary lesions with inadequate compensatory enlargement versus lesions with adequate compensatory enlargement. Design: 35 angiographically significant coronary lesions were examined by intravascular ultrasound (IVUS) during motorised transducer pullback. Segments 20 mm in length were analysed using a validated automated three dimensional analysis system. IVUS was used to classify lesions as having inadequate (group I) or adequate (group II) compensatory enlargement. Results: There was no significant difference in quantitative angiographic measurements and the IVUS minimum lumen cross sectional area between groups I (n = 15) and II (n = 20). In group I, the vessel cross sectional area was 13.3 (3.0) mm 2 at the lesion site and 14.4 (3.6) mm 2 at the distal reference (p < 0.01), whereas in group II it was 17.5 (5.6) mm 2 at the lesion site and 14.0 (6.0) mm 2 at the distal reference (p < 0.001). Vessel and plaque cross sectional areas were significantly smaller in group I than in group II (13.3 (3.0) v 17.5 (5.6) mm 2, p < 0.01; and 10.9 (2.8) v 15.2 (4.9) mm 2, p < 0.005). Similarly, vessel and plaque volume were smaller in group I (291.0 (61.0) v 353.7 (110.0) mm 3, and 177.5 (48.4) v 228.0 (92.8) mm 3, p < 0.05 for both). Lumen areas and volumes were similar. Conclusions: In lesions with inadequate compensatory enlargement, both vessel and plaque volume appear to be smaller than in lesions with adequate compensatory enlargement.